Blame or gain? Is institutional trust impacted by the perception of political influence in state-owned enterprises? - Tobias Alexander Krause; Igor Ivanov; Marcus Sidki (Frankfurt University of Applied Sciences, Fachbereich 3: Wirtschaft und Recht, 2023)
Investigating institutional trust has a strong tradition in public administration research (Bouckaert and Van de Walle 2003; Van de Walle et al. 2008; Grimmelikhuijsen et al. 2013). Blame attribution theory suggests that citizens may blame politicians for serious distrust in public service providers, however there is only scarce evidence with respect to municipally owned corporations in a private law context (Bisgaard 2015; Van den Bekerom et al. 2021). Considering a large-scale survey experiment on 2,023 German citizens, we investigated whether citizen trust in local energy providers is affected by perceptions of political influence. Evidence suggests that there is a small bias effect of perceived influence, however this effect contradicts with the blame attribution hypothesis. We find that citizens are much more positive towards direct political influence than predicted. – – Die Untersuchung von institutionellem Vertrauen hat eine lange Tradition in der Forschung zur öffentlichen Verwaltung (Bouckaert und Van de Walle 2003; Van de Walle et al. 2008; Grimmelikhuijsen et al. 2013). Die Theorie der Schuldzuweisung legt nahe, dass Bürgerinnen und Bürger Politikerinnen und Politikern die Schuld für ernsthaftes Misstrauen gegenüber öffentlichen Dienstleistungsanbietern geben könnten, allerdings gibt es nur wenig Belege für kommunale Unternehmen in einem privatrechtlichen Kontext (Bisgaard 2015; Van den Bekerom et al. 2021). Anhand eines groß angelegten Umfrageexperiments mit 2.023 deutschen Bürger:innen haben wir untersucht, ob institutionelles Vertrauen der Bürger:innen in lokale Energieversorger durch die Wahrnehmung des politischen Einflusses tangiert wird. Die Ergebnisse deuten darauf hin, dass es einen kleinen Verzerrungseffekt des wahrgenommenen Einflusses gibt, der jedoch im Widerspruch zur Hypothese der Schuldzuweisung steht. Wir stellen fest, dass die Bürger:innen dem direkten politischen Einfluss gegenüber viel positiver eingestellt sind als vermutet.
urn:nbn:de:bsz:946-opus4-68794
Keywords: 330